Cervical mediastinoscope: a cardiothoracic training centre experience in Malaysia - Aimanan, Karthigesu; Nor, Mohamad Arif Bin Muhammad; Padmanaban, Balaji (International Surgery Journal, 2016)
Mediastinoscopy since the introduction in year 1959 has remained a useful investigation tool for mediastinal lymphadenopathies. It is also commonly used for preop staging of lung carcinoma. However with the introduction of non-invasive methods, mediastinoscopy technique became least preferred by surgeons and training centres. We have reported a case serie of thirty mediastinoscopies performed in our setting, highlighting on diagnostic accuracy and safety. We believe mediastinoscopy still has a beneficial role for investigation of mediastinal lesions despite availability of minimally invasive methods.